Private Label Price Rigidity during Holiday Periods - Georg Müller; Mark Bergen; Shantanu Dutta; Daniel Levy (Bar-Ilan University, Department of Economics, 2005)
Using weekly retail transaction scanner price data from a large U.S supermarket chain, we find significantly higher retail price rigidity for private label products than for nationally branded products during the Christmas and Thanksgiving holiday periods relative to the rest of the year. The finding cannot be explained by changes in holiday period promotional practices because we find that private label promotions appear to diminish at least as much as national brands. The increased rigidity of private label products relative to national brands is only partially accounted for by increased rigidity of wholesale prices. After ruling out other potential explanations, we suggest that the higher private label price rigidity might be due to the increased emphasis on social consumption during holiday periods, raising the customers' value of nationally branded products relative to the private labels.
Keywords: E12; E31; L11; L20; L16; M21; M31; 330; Price Rigidity; Holidays; Private Label; National Brand; Social Consumption